Clinical use of the serum bactericidal test to guide therapy in pediatric patients with penicillin and cephalosporin-nonsusceptible pneumococcal meningitis - Lin, Yu-Chen; Wang, Ruay-Shyang; Huang, I-Fei; Hsieh, Kai-Sheng; Chiou, Christine C. (Journal of Pediatric Infectious Diseases, 2007)
We report four pediatric patients with penicillin and cephalosporin-nonsusceptible pneumococcal meningitis who were treated with dexamethasone for the first four days of vancomycin therapy. Serum and cerebrospinal fluid bactericidal tests were performed to measure in vivo activity of vancomycin in the presence of dexamethasone. Favorable outcome was achieved in all four patients.
Keywords: Dexamethasone; serum bactericidal test; pneumococcal meningitis; resistant; vancomycin